Digital Counter-Narrative Strategy: A Model for Preventing Radicalism Through Social Media - Benny Erwin; Marsela (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2026)
This research analyses the development of the 4C Model (Context, Communication, Collaboration, Connection) as a digital counter-narrative strategy to prevent the spread of radicalism on social media. This study uses a literature review of 25 journal articles published between 2015 and 2024 to develop a comprehensive strategic framework for digital radicalism prevention efforts. The research data were collected through a systematic review of academic articles from Google Scholar, focusing on digital counter-narrative strategies and social media radicalisation. The study adopted Chris Heuer's 4C framework in data analysis. The results show that the 4C Model offers an effective approach to developing digital counter-narrative strategies. Context emerges as the fundamental component determining implementation success, demonstrated through the importance of understanding audience characteristics and local context. Communication requires multimodal approaches and authentic storytelling, while multi-stakeholder collaboration proves crucial in building program credibility. Connection through active digital community building becomes key to program sustainability. The research provides practical recommendations for implementing the 4C Model in the Indonesian context, including the development of a local content database and a structured monitoring system. The Model requires continuous adaptation to the dynamic changes in the digital landscape and target audience characteristics.